A long term study on Effectiveness and safety of Ivabradine versus Metoprolol on Heart rate and LVEF in post myocardial infarction patients- A tertiary hospital based study - KS, Abseer; M, Midhun; K, Venkatesh Bhat; Surendran, PK (Bangladesh Journal of Medicine, 2022)
Background: Tachycardia and heart failure are a major concern in post myocardial infarction (PMI) patients and a therapeutic challenge. Beta blockers, the first choice drugs used have certain disadvantages. Ivabradine known to reduce heart rate was compared with Metoprolol for their benefits and side effects. The aim of the study is to analyze the effects of Ivabradine on heart rate and LVEF in comparison with Metoprolol at fixed doses over a period of 12 months from the time of discharge. Methods: 278 MI patients were grouped and observed for 12 months for the effect of Ivabradine and Metoprolol drugs on their heart rate (HR) and LVEF values. Patients with acute inferior wall STEMI, HR above 70/minute were included. All patients were on treatment for 12 months. Patients likely to develop cardio-pulmonary complications excluded. MI was confirmed on ECG and serial CK-MB/ troponin T measurements and 2D ECHO. Patients were with Holter monitors. Results: 278 patients were grouped as Ivabradine group wherein 138 patients (Ivabradine 5mg twice daily) and Metoprolol group 140 patients (Metoprolol 25 mg twice daily). All the risk factors were similar in both the groups. The mean HR and LVEF values were similar in both the groups. The range of HR was 64 to 86 beats per minute in all patients. The symptomatologies among the patients of both the groups were also similar. Reduction of HR was from 76.43±7.3 to 62.55±1.05 and in Metoprolol group from 77.51±4.50 to 61.45±2.35 beats per minute 13 (09.24%) patients from Ivabradine group and 19 (13.57%) patients from Metoprolol group showed a heart rate less than 60/bpm, others had heart beats > 60/mt. Conclusion: Ivabradine was a competitive bradycardic drug in comparison to Metoprolol in early Post MI patients. It had similar action on LVEF as Metoprolol. It could be potentially used an alternative anti-tachycardia drug with no other cardiovascular side effects and wherever â-blockers are contraindicated. Bangladesh J Medicine 2022; 33: 252-258